Re-imagining global health through social medicine. Issue 10 (3rd October 2019) - Adams, Vincanne; Behague, Dominique; Caduff, Carlo; Löwy, Ilana; Ortega, Francisco
ABSTRACT: The conceptual and practical work done by social medicine and global health have often overlapped. In this paper, we argue that new efforts to apprehend 'the social' in social medicine offer important insights to global health along five lines of critical analysis: (1) reconfigurations of the state and new forms of political activism, (2) philanthrocapitalism and the economisation of life, (3) The economy of attention, (4) anthropogenic climate change, and (5) the geopolitics of North and South.